Effect of Soil Salinity on Thermal Behavior of Sandy Soils Under a Sahara Climate - Djihad Bennaceur; Nadia Laredj; Mustapha Maliki; Hanifi Missoum (Science, Engineering and Technology)
Soil salinity represents a harmful environmental problem that occurs either naturally or as a consequence of ineffective management practices by humans, especially in arid regions. Assessing ground temperature profile represents an important indicator for evaluating the performance of geothermal systems, used in air conditioning of building. This paper proposes a conceptual and numerical model for predicting the hydrothermal behavior of unsaturated soils. The effect of soil salinity was investigated in this research. Two soil types (sandy and sandy loam) were studied under three salinity levels. Moreover, the arid meteorological conditions of Sahara Desert were considered in the developed model. According to the results, it appears that sandy soils exhibit optimal thermal behavior at a moderate salinity concentration of C = 0.1 M, with increased surface temperatures during warmer periods and better heat conservation in colder conditions. Conversely, sandy loam soils respond most effectively at a higher salinity concentration of C = 0.2 M, particularly excelling in heat retention during the summer months. These results emphasize the intricate interaction between soil composition and salinity in regulating temperature patterns, providing important knowledge for enhancing soil management practices that are customized to particular soil types and environmental factors, with potential implications for geothermal applications.